Pursuing Freedom: Simone de Beauvoir and Hannah Arendt - Gardiner, Rita Ann (Sapere Aude, 2013)
How do we judge what is right while, at the same time, respect the freedom of others? In considering this question, I bring Simone de Beauvoir and Hannah Arendt into dialogue to better understand how the pursuit of freedom necessitates a willingness to judge others. In my discussion, I explore how these writers treat the themes of ambiguity, oppression, and revolution. By comparing how they relate these themes to freedom, we see how liberty is interconnected with personal accountability, and a willingness to question our beliefs. It is when we are unwilling to engage in an ongoing dialogue, I argue, that we risk losing that which is most precious to us, namely, freedom. I begin by examining Beauvoir’s Ethics of Ambiguity to see how she connects ambiguity with ethical action. Then, I consider how ethical action is sometimes obscured by self-centered desires, which bar us from thinking about how our actions may negate the freedom of others. Next, I look at their different approaches to questions of freedom as it relates to eradicating oppression. Finally, I examine the ways in which Beauvoir and Arendt show that the pursuit of freedom requires us to take a personal stance against injustice in order to respect the dignity of others. In so doing, we engage in an ethical relationship with the world.